2010
DOI: 10.1161/circulationaha.110.947002
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Resulting From Congenital Heart Disease Among Children and Adults in the United States, 1999 to 2006

Abstract: Background-Previous reports suggest that mortality resulting from congenital heart disease (CHD) among infants and young children has been decreasing. There is little population-based information on CHD mortality trends and patterns among older children and adults. Methods and Results-We used data from death certificates filed in the United States from 1999 to 2006 to calculate annual CHD mortality by age at death, race-ethnicity, and sex. To calculate mortality rates for individuals Ն1 year of age, population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
347
3
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 524 publications
(364 citation statements)
references
References 44 publications
8
347
3
6
Order By: Relevance
“…These findings confirm the results of Jacobs et al who, in a Hong Kong population, found that white children had more left ventricular obstructive lesions, whereas Chinese children had more right ventricular outflow tract lesions [6]. Race and ethnic differences in mortality in CHD have been demonstrated by Gilboa et al [7]. By means of death certificates filed in the United Fig.…”
Section: Race and Ethnicitysupporting
confidence: 89%
“…These findings confirm the results of Jacobs et al who, in a Hong Kong population, found that white children had more left ventricular obstructive lesions, whereas Chinese children had more right ventricular outflow tract lesions [6]. Race and ethnic differences in mortality in CHD have been demonstrated by Gilboa et al [7]. By means of death certificates filed in the United Fig.…”
Section: Race and Ethnicitysupporting
confidence: 89%
“…[1][2][3][4] Although the outcome has improved over the past decades, morbidity and mortality remain high, especially in infants with critical congenital heart disease (CCHD) in which circulation is dependent on ductal or interatrial shunting. [5][6][7] A large Swedish populationbased study reported that the risk of being discharged with undiagnosed duct-dependent CCHD was 28%. 8 Recently, Peterson et al 9 reported in a US population-based study that 29.5% of 3746 infants with CCHD were diagnosed late, after 3 days of birth.…”
mentioning
confidence: 99%
“…Congenital heart disease (CHD) and early acquired heart disease (EAHD) are of special importance in adolescents as they may impact their subsequent health as they age [2], [3]. Many studies which investigated the prevalence of CHD in fetal and newborn populations found fewer subjects than in population studies of older children and adolescents [4], [5].…”
Section: Introductionmentioning
confidence: 99%